Risk of Rare Disasters, Euler Equation Errors and the Performance of the C-CAPM - Olaf Posch; Andreas Schrimpf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper shows that the consumption-based asset pricing model (C-CAPM) with low-probability disaster risk rationalizes large pricing errors, i.e., Euler equation errors. This result is remarkable, since Lettau and Ludvigson (2009) show that leading asset pricing models cannot explain sizeable pricing errors in the C-CAPM. We also show (analytically and in a Monte Carlo study) that implausible estimates of risk aversion and time preference are not puzzling in this framework and emerge as a result of rational pricing errors. While this bias essentially removes the pricing error in the traditional endowment economy, a production economy with stochastically changing investment opportunities generates large and persistent empirical pricing errors.
Keywords: E21; G12; O41; 330